Dinamika Pendapatan Asli Daerah dan Transfer Fiskal terhadap Keberlanjutan Pertumbuhan Ekonomi Kabupaten/Kota di Pulau Lombok pada Tahun 2015-2024 - Rizqiyati Amalyah, Dewi; Suriadi, Irwan (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2025)
This study aims to analyze the impact of Local Own-Source Revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), and Revenue Sharing Fund (DBH) on the economic growth of regencies and cities on Lombok Island during the 2015–2024 period. The main issue addressed is the high dependence of local governments on fiscal transfers from the central government, which may weaken fiscal autonomy and the effectiveness of decentralization. The study employs a quantitative approach based on panel data sourced from the Central Bureau of Statistics (BPS) and the Directorate General of Fiscal Balance (DJPK), analyzed using the Fixed Effect Model through EViews 12 software. The results indicate that all variables PAD, DAU, DAK, and DBH have a positive and significant effect on the Regional Gross Domestic Product (RGDP), used as a proxy for economic growth. Simultaneously, these variables explain 99% of the variation in economic growth on Lombok Island. These findings highlight that increasing fiscal capacity both through local revenue optimization and productive central transfers plays a crucial role in fostering sustainable regional economic growth. Therefore, local fiscal policy should focus on enhancing fiscal independence, improving public spending efficiency, and strengthening adaptive fiscal synergy between central and regional governments.